Analysing Product Quality, Service Quality and Customer Satisfaction A Case Study of ‘Kedai Rakyat 1 Malaysia’ Stores - Gondal, Kunal (2013)
Only once you are aware of the customers’ perception of business, the service and the products offered, one would have a clear idea of whether the business is going in the right direction or not. An important strategic objective in a retail store is customer perception. In order to survive in a competitive setting and achieve profitability, retailers need to ensure that they respond adequately to customers’ requirement. Although there exists a number of factors which relate to customer requirement, but the most important aspects are those of product quality and service quality. Hence firms should focus on two key aspects namely service quality and product quality which are critical to customer satisfaction. The purpose of this thesis is to find out how ‘Kedai Rakyat 1 Malaysia’ store’s customers’ perceive them. The study looks at the customers experience and perception of the service they receive and the products that are offered. The first objective of the study is therefore to analyse the existing customers’ perceptions of the store, the products and the service. The second objective is to investigate how the KR1M can use this knowledge and develop the business and customer service even further. The answers to the stated research were gathered by conducting a quantitative questionnaire among the KR1M’s customers. The results showed the strengths and the weaknesses of ‘Kedai Rakyat 1 Malaysia’ stores. A number of strategies to enhance the product quality and service quality are proposed in latter part of this thesis. The study also shows that perception of customers about product quality and service quality are equally important to build up their satisfaction.